SOSIALISASI DAN INISIASI BADAN USAHA MILIK DESA (BUMDES) DESA MEJASEM BARAT KECAMATAN KRAMAT KABUPATEN TEGAL - agnes dwita susilawati; Budi Susetyo; Yuniarti Herwinarni; Mahben Jalil; Mei Rani Amalia (Universitas Majalengka, 2022)
BUMDes is a form of strengthening village economic institutions and is a tool for utilizing the local economy, whose formation aims to improve the economic welfare of rural communities through the development of economic businesses and local sources of income. Its establishment is in line with Law No. 6 of 2004 concerning Villages and Permendes PDTT RI No. 4 of 2015. The purpose of this service activity is to find out the process of forming a good and professional West Mejasem Village BUMDes in accordance with its purpose. In this method of devotion there are 3 (three) stages; The first stage, socialization and initiation about the process of forming BUMDes, the second stage, participants get material